Principals’ Perceived Effect of Conflict Resolution Procedures on Teachers' Job Satisfaction: A Case Study in Government Technical Colleges of Kano State, Nigeria - Isaac John Ibanga; Idris Mustapha Abdullahi; Garba Zakariya’u (The Indonesian Institute of Science and Technology Research, 2023)
The study aimed to investigate the impact of conflict resolution procedures on teachers' job satisfaction in Government Technical Colleges in Kano State, Nigeria. The population of the study was 367 respondents, including 15 principals and 352 technical teachers. A sample size of 201 respondents was determined using the correlational research design. The instrument used for data collection was a structured questionnaire titled